The protective effect of high-pressure ischemic preconditioning on rowing performance during consecutive 2000-m efforts - Weng, M.-C.; Lee, P.-C.; Dai, X.; Chiu, C.-H.; Ho, C.-C.; Hsu, S.-M.; Chen, C.-H. (International Journal of Sports Physiology and Performance, 2026)
Purpose: This study examined the effects of low- and high-pressure ischemic preconditioning (LIPC and HIPC) on muscle oxygenation, physiological responses, and performance during repeated 2000-m rowing trials. This was a counterbalanced, repeated-measures crossover study.